In Defense of Causal Presentism - Virmajoki Veli (The University of Chicago Press, 2025)
In this article, I defend causal presentism in the historiography of science. In causal presentism, the historiography of science studies events, processes, and practices that were causally relevant to the development of the present science. I argue that causal presentism has three main virtues. First, causal presentism avoids the conceptual problems that the historiography of science has recognized at its core. Second, causal presentism provides a clear account of what counts as historical explanatory understanding about science. Third, causal presentism enables novel ways to address several conceptual and methodological problems in the historiography of science. The conclusion is that causal presentism is a distinctively strong position with respect to the historiography of science.